India’s Emergence as a Regional Education Hub - Khare, Mona (International Higher Education, 2015)
India’s rising academic leadership in the South Asian region is largely seen as a fallout of its Liberalisation Policy and the formation of numerous regional cooperation blocks/groups/associations. India has widened its presence in the region through various modes such that it is no longer identified as just a North-South recipient nation of earlier times. The time is ripe when India can further consolidate its position as a regional education hub by way of systematic strategic planning.